SOCIAL-PSYCHOLOGICAL STRUCTURE OF THE IMAGE OF A FOOTBALL COACH AS THE SUBJECT OF SPORT’S ACTIVITIES - Petrovska, Tetiana; Malinowskiy, Andriy (PSYCHOLOGICAL JOURNAL, 2017)
The modern view of the training process involves not only the analysis of the influence of the coach to athlete, but also a certain interest in the coach's personality. Image largely determines the effectiveness of a coach. Some authors emphasize the importance of the problem of forming an effective, efficient image of a coach that helps to improve the performance of competitive activities of athletes. At present, the problem of the image of a sports coach remains understudied. Objective. A theoretical analysis of the problem of the influence coach image on the effectiveness of sports activities; theoretical and empirical support for the social and psychological components of a sports coach image. Results. Belonging in a sports team and the role of the coach in it for achievement of high sports result is a categorical value for athletes. The image of a coach influences the quality and content of the communication and is formed through a form of interpersonal reflection: reflection sensory (appearance), generalized reflection (the concept), the reflection of affective (attitude), the concrete tool (activities). Image structure includes cognitive, affective and behavioral component of the coach personality. Conclusion. The image of a successful coach can be seen as emotionally charged mental image, which in the perception of athletes is identified with the group and solo sports success, and which is able to induce an increase in the effectiveness of athletes action.